ABDOMINAL COMPARTMENT SYNDROME IN PATIENTS WITH ACUTE CEREBROVASCULAR FAILURE (LITERATURE REVIEW) - Sabirov D.M., Rosstalnaya A.L., Sulaymanov Kh.O. (Central Asian Journal of Medicine, 2025)
This article examines and analyzes the causes, features of the pathophysiology mechanisms of intra-abdominal pressure increase, as well as modern aspects of diagnosing and treating patients with abdominal-compartment syndrome (ACS) in critically ill patients with acute cerebrovascular insufficiency. An analysis of literature devoted to the issues of intra-abdominal hypertension (IAH), ASH, and their impact on organs and systems, with a particular emphasis on neurological consequences, has been conducted. ACS is a multi-organ pathological condition caused by a persistent increase in intra-abdominal pressure above 20 mm Hg, combined with signs of organ dysfunction. Diagnosis requires active monitoring of VBP and calculation of abdominal perfusion pressure. Untimely detection and correction of HCV/ACS significantly worsen the outcome of critical conditions. Conclusions: HCV and ACS require immediate clinical evaluation and intervention. Further research aimed at studying the impact of ACS on the central nervous system is necessary.